Sub-Surface Investigation of Khashim Al-Ahmer Gas Field Using Seismic Reflection Data - Z.Khorshid, Salman; I. Owiad, Jinan (Iraqi Journal of Science, 2023)
This paper is carried out to detect the subsurface structures that have geologicaland economical importance by interpreting the available reflection seismic data ofan area estimated to be about (740) km2. The Khashim Al-Ahmer structure is partialof series structures of (Injana – Khashim Al-Ahmer – Mannsorya) from the (NW tothe SE), it is located within for deep faulted area. The component of the oneelongated dome of asymmetrical of structure which has(SW) limb more steeper thanthe (NE) limb.Twenty three seismic sections had been interpreted for two seismicsurveys and the total length of all seismic lines is about (414.7) Km. Interpretationof seismic data was focused on two reflectors (Fatha and Jeribi) Formations whichbelong to Lower and Middle Miocene age. The reflectors were picked and identifiedby tying them directly to well Khashim Al-Ahmer-2, the Lower Fars(FathaFormation) reflector was picked at TWT ranging from (0.3-1.7) sec while the Jeribireflector was picked at TWT ranging from (0.83- 2) sec. The depth map showed thatthe depth of the Jeribi Formation ranges between (1100 - 2000) m, and the velocitymaps of studied reflector showed increase of velocity values to the south east andthere is a local closure in the north east of the study area and decrease to the northwest and the velocity values decrease and give closure situated below well KA-2.The magnitude of velocity values ranges in Jeribi velocity map from (3100 to 3400m/sec). Seismic attributes techniques (instantaneous phase) is important to detect thehydrocarbon accumulation on seismic sections. Major faults (reverse and thrust)were picked along study area on instantaneous phase sections. These faults extend inNW-SE trend and the displacement of the fault ranges between (400-660) m. Thevelocity, time and depth maps were drawn by the aid of GeoFrame and petrelsoftware.